Admixture in Humans of Two Divergent Plasmodium knowlesi Populations Associated with Different Macaque Host Species - Paul, C.S; Balbir, Singh; Fread, Anderios; Shamilah, Hisam; Asmad, matusop; Clemens, H. M. Kocken; Samuel, A. Assefal; Craig, W. Duffy; David, J. Conway (Researchgate, 2015)
Human malaria parasite species were originally acquired from other primate hosts and subsequently became endemic, then spread throughout large parts of the world. A major zoonosis is now occurring with Plasmodium knowlesi from macaques in Southeast Asia, with a recent acceleration in numbers of reported cases particularly in Malaysia. To investigate the parasite population genetics, we developed sensitive and species-specific microsatellite genotyping protocols and applied these to analysis of samples from 10 sites covering a range of >1,600 km within which most cases have occurred. Genotypic analyses of 599 P.knowlesi infections (552 in humans and 47 in wild macaques) at 10 highly polymorphic loci provide radical new insights on the emergence. Parasites from sympatric long-tailed macaques (Macaca fascicularis) and pig-tailed macaques (M. nemestrina) were very highly differentiated (FST = 0.22, and K-means clustering confirmed two host-associated subpopulations). Approximately two thirds of human P. knowlesi infections were of the longtailed macaque type (Cluster 1), and one third were of the pig-tailed-macaque type (Cluster 2), with relative proportions varying across the different sites. Among the samples from humans, there was significant indication of genetic isolation by geographical distance overall and within Cluster 1 alone. Across the different sites, the level of multi-locus linkage disequilibrium correlated with the degree of local admixture of the two different clusters. The widespread occurrence of both types of P. knowlesi in humans enhances the potential for parasite adaptation in this zoonotic system.